Divergent Expression of SPARC, SPARC-L, and SCPP Genes During Jawed Vertebrate Cartilage Mineralization - Romero, Adrian; Leurs, Nicolas; Muñoz, David; Debiais-Thibaud, Mélanie; Marcellini, Sylvain (Frontiers in Genetics, 2021)
While cartilage is an ancient tissue found both in protostomes and deuterostomes, its calcification evolved more recently, within the vertebrate lineage. SPARC, SPARC-L and the SCPP members (Secretory Calcium-binding PhosphoProtein genes which evolved from SPARC-L) are major players of dentine and bone calcification, but their involvement in the emergence of the vertebrate calcified cartilage remains unclear. We performed in situ hybridization on mineralizing cartilaginous skeletal elements of the frog Xenopus tropicalis (Xt) and the shark Scyliorhinus canicula (Sc) to examine the expression of SPARC (present in both species), SPARC-L (present in Sc only) and the SCPP members (present in Xt only). We show that while calcifying cartilage expresses SPARC (but not SPARC-L) in Sc, it expresses the SCPP genes (but not SPARC) in Xt, and propose two possible evolutionary scenarios to explain these opposite expression patterns. In spite of these genetic divergences, our data draw the attention on an overlooked and evolutionarily conserved peripheral cartilage subdomain expressing SPARC or the SCPP genes and exhibiting a high propensity to mineralize.